(untitled) - Gadner, Johannes (New York, 2004)
The organization, processing and representation of knowledge becomes increasingly important in all scientific and business contexts. This book focuses on qualitative methods for knowledge organization and their contributions to knowledge-based issues of marketing management research. Besides theoretical discussions of different approaches to and definitions of knowledge, as well as methods for knowledge organization, several case studies in the field of marketing management are presented. Questions of research design, adequate choice of methodologies and practical relevance of the results are addressed.
Keywords: Gabek (computer file),Knowledge, theory of,Knowledge management